EARLY EVOLUTION OF THE DUWIBONG UNIT OF THE LOWER PALEOZOIC JOSEON SUPERGROUP, KOREA: A NEW VIEW - Kim Y.; Lee Y.I. (My University, 2006)
This study proposes the revised stratigraphy of the lower part of the Duwibong Unit of the lower Paleozoic Joseon Supergroup that the Myobong Formation is the lowermost stratum. The Jangsan Formation, which has long been regarded as the lowermost stratum of the Unit, is likely to be of late Proterozoic in age. It is also proposed that the Myeonsan and Myobong formations are of coeval age and that the Myeonsan Formation formed in the early stage is interpreted to be the local proximal facies which was overlain by the Myobong Formation in the late stage. This new interpretation is based on the presence of the unconformity between the Jangsan and Myobong formations observed in two areas (Dongjeom area, Taebaek City and Deogam area, Imgye-Myeon, Jeongseon-Gun). Sandstone facies in the topmost part of the Myeonsan Formation is gradually overlain by siltstone to mudstone facies of the Myobong Formation. In addition, Myobong mudstone is geochemically similar to Myeonsan mudstone. The similarity in lithologies among Jangsan sandstone, quartzarenite gravelly clasts in the Myeonsan Formation and the newly defined late Proterozoic stratum (Kim and Lee, 2003a), immediately underlying the Myeonsan Formation provides additional evidence that the Jangsan Formation is not the lowermost stratum of the Duwibong Unit but the source rocks of quartzarenite gravelly clasts of the Myeonsan Formation.
Keywords: LOWER PALEOZOIC; JOSEON SUPERGROUP; TAEBAEKSAN BASIN; JANGSAN FORMATION; MYOBONG FORMATION; Proterozoic; Precambrian::Proterozoic; Докембрий::Протерозой